Quantitative sensory testing (QST): English version = Quantitative sensorische Testung (QST) - Mücke, Martin; Cuhls, H.; Radbruch, L.; Baron, R.; Maier, C.; Tölle, T.; Treede, Rolf-Detlef; Rolke, R. (Der Schmerz, 2021)
Quantitative sensory testing (QST) is a standardized and formalized clinical sensitivity test. Testing describes a subjective (psychophysical) method that entails a cooperation of the person to be examined. Within its framework, calibrated stimuli are applied to capture perception and pain thresholds, thus providing information on the presence of sensory plus or minus signs. The presented QST battery imitates natural thermal or mechanical stimuli. The aim is to acquire symptom patterns of sensory loss (for the functioning of the thick and thin nerve fibers) as well as a gain of function (hyperalgesia, allodynia, hyperpathia) with a simultaneous detection of cutaneous and deep tissue sensibility. Most of the tested QST parameters are normally distributed only after a logarithmic transformation (secondary normal distribution)—except the number of paradoxical heat sensations, of cold and heat pain thresholds, and vibration detection thresholds. A complete QST profile can be measured within 1 h. QST is suitable not only for clinical trials but also in practice as a diagnostic method to characterize the function of the somatosensory system—from the peripheral nerve fiber receptor to the projection pathways to the brain.